Coenzyme A thioester, free and protein-bound amino acid, B vitamin and respiratory quinone compositions in the digestive system of Antarctic krill, Euphausia superba, sampled in January, March and May - Heyen, Simone; Töpker, Verena; Kopke, Bernd; Cakić, Nevenka; Hüppe, Lukas; Meyer, Bettina; Wilkes, Heinz
This dataset contains the seasonal composition of coenzyme A thioesters, amino acids, B vitamins ans respiratory quinones from the digestive system of Antarctic krill, Euphausia superba. Krill was caught with a continuous krill pumping system in May of 2021 in the Bransfield Strait and in January and March of 2022 at the South Orkney Islands. The stomach, digestive gland and hind gut were dissected and analysed. Samples were extracted with an optimized Bligh&Dyer protocol. Coenzyme A thioesters, B vitamins and respirtory quinones were measured with liquid chromatography - mass spectrometry, amino acids with gas chromatography - mass spectrometry. Amino acids and B vitamins were identified with standards. For coenzyme A thioester, identification was based on authentic standards as well as characteristic fragmentation patterns to identify sum formulas of unknown CoAs. In the case of respiratory quinones, the identification was also based on characteristic fragmentation patterns and retention orders.